Aplikasi Pengenalan Alat Musik Pada Anak Usia Dini - Yusup Miftahuddin; Marisa Premitasari; Daniel Barus; Fakhrudin Rizky Husaini; Noer Fadillah (Universitas Katolik Widya Karya Malang, 2023)
The development of music from the past until now continues to grow, from traditional musical instruments to modern musical instruments that are currently widely used. However, today's children or adolescents are more interested in modern musical instruments such as guitars, saxophones, violins and other modern musical instruments than traditional musical instruments such as suling, gendang and other traditional musical instruments. So it is necessary to teach from an early age by introducing both traditional and modern musical instruments. By taking advantage of technological developments, especially in multimedia technology, we need a system that can facilitate teaching through computers or commonly called CAI (Computer Assisted Instruction). This was done because the Mekar Arum Kindergarten children were still not interested in musical instruments. So we need an application to introduce musical instruments that can be used in learning while playing to attract children's attention. With this application, it can make it easier for teachers to teach introduction to musical instruments for young children without having to meet children at kindergartens and make it easier for children to recognize musical instruments and be more interested in traditional and musical instruments modern.